Synthesis and Characterization of N-(Pyrrolidinobenzyl)-benzamide and its Complexes with Cobalt(II), Nickel(II), Copper(II) and Zinc(II) - VISWANATHAN, M.; RAJI, V. (Asian Journal of Chemistry, 2010)
A new Mannich base, N-(pyrrolidinobenzyl)benzamide, derived from pryrrolidine, benzamide and benzaldehyde and its complexes with cobalt(II), nickel(II), copper(II) and zinc(II) have been synthesized and characterized. Their chemical composition have been established from microanalytical, magnetic, molar conductance, spectral, thermal and X-ray powder diffraction studies. In these complexes, N-(pyrrolidinobenzyl) benzamide acts as a bidentate ligand and all the complexes exhibit square planar geometry. The monomeric and non-electrolytic nature of the complexes are evidenced by their conductance and magnetic susceptibility data. The antimicrobial activity of the ligand and the complexes are also studied. The complexes have higher activity than that of the ligand.